Hydrocarbon distribution pattern and logging identification in lacustrine fine-grained sedimentary rocks of the Permian Lucaogou Formation from the Santanghu basin. (15th June 2018) - Liu, Guoheng; Liu, Bo; Huang, Zhilong; Chen, Zhiyuan; Jiang, Zhenxue; Guo, Xiaobo; Li, Tingwei; Chen, Lei
Highlights: Three types of lithofacies were developed in the fine-grained sedimentary rocks of the Lucaogou Formation. The resistivity log combined with tri-porosity logging suites was selected to differentiate the three lithofacies. Commercial oil production mainly appears in organic-rich massive tuffaceous shale lithofacies. Uplift belts away from erosion area and developing thick tuffaceous shale will be area with the most potential. Abstract: A series of qualitative descriptions and quantitative analyses was used to determine the lithofacies characteristics and hydrocarbon distribution pattern of Lucaogou Formation fine-grained sedimentary rocks in the Santanghu Basin. The qualitative descriptions include core description, petrographic thin section observation, fluorescence observation, cathode luminescence observation and scanning electron microscope (SEM) observation. The quantitative analyses include X-ray diffraction, total organic content analysis, programmed pyrolysis, Soxhlet extraction, vitrinite reflectance, maceral composition, porosity and permeability analysis, and oil saturation analysis. Three main types of lithofacies were identified in this study area: organic-rich massive tuffaceous shale lithofacies (RMTSL), organic-rich laminated and cloddy diamictite lithofacies (RLCDL) and organic-lean massive dolomite lithofacies (LMDL). RMTSL mainly includes massive shale and tuffaceous shale. Quartz and clay minerals are the major components of rocks from this lithofacies. RLCDL develop lamina and a cloddy structure. Rocks from this lithofacies chiefly consist of dolomite and quartz. LMDL mainly contains massive bedding fine-grained carbonate rocks. Dolomite accounts for the main portion of these rocks. RMTSL contains the highest content of free hydrocarbon and solid organic matter. Moreover, higher porosity was observed in RMTSL. LMDL contains the lowest solid organic matter content and develops the least pores. RLCDL develop the largest number of cracks and fractures. Resistivity logging (RD) combined with tri-porosity logging suites were finally selected to differentiate the three lithofacies. The response characteristics of RMTSL should be high acoustic time (AC), low density (DEN), high compensated neutron logging (CN) and high resistivity logging (RD). On the contrary, the response characteristics of LMDL are low acoustic time (AC), high density (DEN), low compensated neutron logging (CN) and low resistivity logging (RD). Commercial oil production mainly appears in RMTSL. Uplift belts that are away from erosion areas and develop thick RMTSL will be the area with the most potential. Hence, the Mazhong uplift belt is the most favourable area for the accumulation of hydrocarbon on a large scale.